A Study on Comparison on Key Financial Parameters of Players Within an Industry with Similar Parameters in Nifty - A Study of Steel Companies - Sharma, S. R.; Tiwari, Prakash; Verma, Hemraj (Indian Journal of Finance, 2009)
Comparison of financial parameters between a standard market "bundle" and individual companies is a common analysis carried out by financial observers. While this is no doubt capable of giving a lot of insights into the company’s performances, another useful measure that is likely to throw greater light is the comparison between the bundle and the industry concerned. The representative index or group is supposed to contain all the significant value creators in the country and the comparison of financial parameters for this purpose gives new impetus to the comparison. This study explores the possibility of such comparison as between NIFTY, arguably the index representing the most valuable companies in India, and the principle player in the steel industry. The analysis throws light on some interesting observation which can be used in a larger study for drawing up comparisons.